DESIGN OF A WEB BASED ACADEMIC COUNSELING INFORMATION SYSTEM IN UNIVERSITY: A CASE STUDY OF JAKARTA STATE UNIVERSITY, INDONESIA - ZARINA AKBAR, MAUNA, ERNITA ZAKIAH, MARATINI SHALIHA AISYAWATI (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
This research presents the design of web-based academic counselling information system. The research aims to reveal a design framework for a web-based academic counselling information system integrated with universities, lecturers, students to support academic counselling processes. In the implementation of academic counselling, lecturers and students must work together to create quality guidance. This research is structured as a design-based research approach. This research presents the results of the first cycle of design-based research. The research follows a five step process: (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. A pilot study involved three psychologist and two counsellors as reviewers in Jakarta State University Indonesia. The system examined with ten students during implementation. Feedback from reviewers guided improvements. Overall the web is receptive, easily access when used, and get information directly. Moreover, the web can still be developed such as adding notification features, providing pop-ups with further information as a guide for users, connecting to users email or whatsapp, and being synchronized with the counselor's activity schedule. With this system is expected also to become a web-based academic counselling in order to make information system faculty better in particular and all faculties of university all over Indonesia.